Спектральні характеристики наноструктур типу ядро-оболонка в умовах плазмонного резонансу - Булавінець, Т. О.; Яремчук, І. Я.; Бобицький, Я. В.; Bulavinets, T. O.; Yaremchuk, I. Ya.; Bobitski, Ya. V. (Видавництво Львівської політехніки, 2020)
Здійснено моделювання спектральних характеристик наноструктур типу ядро – оболонка, а саме срібло – золото, срібло – мідь, срібло – діоксид титану та діоксид титану – срібло в умовах локалізованого поверхневого плазмонного резонансу. Показано, що зміною товщини оболонки на металевому чи напівпровідниковому ядрі можна керувати спектральним положенням піка поверхневого плазмонного поглинання у видимій області спектра та оцінено вплив геометричної деформації наноструктур на їхні оптичні характеристики.

In this paper, the spectral characteristics of the core-shell type nanostructures, namely silver – silver, silver – copper, silver – titanium dioxide and titanium dioxide – silver in the conditions of localized plasmon resonance have been theoretically researched for the purpose of their further photonics and plasmonics applications. It is shown that by changing the thickness of the shell on the metal or semiconductor core, one can shift the spectral position of the surface plasmon absorption peak in the visible spectral region and evaluate the influence of deformation of nanostructures on their optical characteristics. It is shown that in the case of bimetallic structures, the spectral position of the absorption and scattering cross sections peaks is not sensitive to changes in the thickness of the shell, only their amplitude changes. In the case of nanostructures such as silver-titanium dioxide there is a clearly pronounced additional peak in the spectra of absorption and scattering cross sections. Such a two-band nature can be explained by the excitation of localized plasmons on two interfaces titanium dioxide/silver and silver/environments. The spectral position of the both peaks of absorption and scattering cross sections is shifted to the long-wave region of the spectrum, when the shell thickness changes and when the nanostructure is deformed (extended) for such type of the nanoshells. The structure of titanium dioxide – silver is characterized by a shift of the second peak into the short-wave region of the spectrum when shell thickness increases and when there are deformations. And the first one is practically not sensitive to such changes. It should be noted that with a certain shell thickness, such structure will have characteristics similar to those of a silver nanoparticle.
Spectral characteristics of the core-shell type nanostructures under plasmon resonance conditions
Keywords: наночастинка; нанооболонка; плазмонний резонанс; переріз поглинання; переріз розсіювання; nanoparticle; nanoshell; plasmon resonance; absorption cross-section; scattering cross-section; 535.341